2013
DOI: 10.1590/s1413-78522013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Artroplastia do ombro na osteoartrose: correlação entre função e parâmetros radiográficos

Abstract: OBJECTIVES: To evaluate the correlation between radiographic parameters and functional assessments of patients with osteoarthritis of the shoulder who underwent shoulder arthroplasty and to describe the functional outcomes of this procedure in our institution. METHODS: We evaluated 21 patients (22 shoulders) who underwent shoulder arthroplasty between 1998 and 2010 and with a minimum follow-up of 12 months. Clinical evaluation was performed using the Constant-Murley scale, UCLA, EVA and by measuring the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Nevertheless, assuming correct patient positioning and x-ray projection as well as correct implant positioning anteversion is very unlikely since anatomical studies showed that humeral head retroversion averages around 30 degrees. 18,19 Furthermore, differentiation of retroversion vs . anteversion has no adverse effect on the calculated inclination angle.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, assuming correct patient positioning and x-ray projection as well as correct implant positioning anteversion is very unlikely since anatomical studies showed that humeral head retroversion averages around 30 degrees. 18,19 Furthermore, differentiation of retroversion vs . anteversion has no adverse effect on the calculated inclination angle.…”
Section: Discussionmentioning
confidence: 99%